KLASIFIKASI JENIS TUMOR OTAK BERDASARKAN CITRA GLIOMA MENGGUNAKAN METODE SUPPORT VECTOR MACHINE - Adam Jordie Sinulingga; Darwis Robinson Manalu; Samuel Manurung (Universitas Methodist Indonesia, 2023)
This study uses the Support Vector Machine method, where this method aims to obtain a classification model that has high accuracy or small error in classifying an image. The development of the medical world today is closely related and cannot be separated from the development of information technology that continues to grow. To be able to distinguish Magnetic Resonance Image (MRI) images detected by brain tumors, it is necessary to carry out a classification process using the Support Vector Machine (SVM) method. So we need an application for classifying brain tumors to facilitate medical work in determining the type of brain tumor disease. Image processing will use 2 types of brain tumors, namely Glioma and Meningioma